(untitled) (Revista de Ciências Agroveterinárias, 2024)
The aim of this study was to evaluate the effect of applying Etefom as a chemical fruit thinner on apple trees grown on the northern plateau of Santa Catarina. The experiment was carried out in the municipality of Monte Castelo, Santa Catarina, in a commercial orchard, under the Eva apple cultivar, with 2,500 plants/ha. The treatments evaluated were: T1 - Manual; T2 - Etefom. T3 - Etefom + manual transfer; T4 - two applications of Etefom. Ethrel® (Etefom) was used at a dose of 2 L/ha. Chemical thinning is efficient when it results in fruit drop; however, it is necessary to use manual thinning. Manual thinning is less costly, but it requires a long period of time per hectare, which can make it unfeasible to manage fruit thinning at the right time, and so the application of chemical thinning becomes an important management tool in apple growing, due to the short time it takes to carry it out.